Microglia regulate GABAergic neurogenesis in prenatal human brain through IGF1 - Diankun Yu; Samhita Jain; Andi Wangzhou; Beika Zhu; Wenyuan Shao; Elena J. Coley-O’Rourke; Stacy De Florencio; JaeYeon Kim; Jennifer Ja-Yoon Choi; Mercedes F. Paredes; Tomasz J. Nowakowski; Eric J. Huang; et al. (Nature, 2025)
Abstract GABAergic neurons are essential cellular components of neural circuits. Their abundance and diversity have increased significantly in the human brain, contributing to the expanded cognitive capacity of humans 1 . However, the developmental mechanism underlying the extended production of GABAergic neurons in the human brain remains elusive. Here we uncovered the microglial regulation of the sustained proliferation of GABAergic progenitors and neuroblasts in the human medial ganglionic eminence (hMGE). We showed that microglia are preferentially distributed in the proliferating zone and identified insulin-like growth factor 1 (IGF1) and its receptor IGR1R as the predicted top ligand–receptor pair underlying microglia–progenitor communication in the prenatal hMGE. Using our newly developed neuroimmune hMGE organoids, which mimic the hMGE cytoarchitecture and developmental trajectory, we demonstrated that microglia-derived IGF1 promotes progenitor proliferation and production of GABAergic neurons. Conversely, IGF1-neutralizing antibodies and IGF1 knockout human embryonic stem-cell-induced microglia abolish the induced microglia-mediated progenitor proliferation. Together, these findings revealed a previously unappreciated role of microglia-derived IGF1 in promoting the proliferation of neural progenitors and the development of GABAergic neurons in the human brain.